Just transitions in agrifood systems must benefit small holder food producers. CGIAR Issue Brief Series for Informing COP 29 | Number 5 - Mukherji, Aditi; Majdalani, R. (CGIAR, 2024)
A just transition is one in which the benefits of the switch to a low-emission, carbon-neutral economy needed to halt the climate crisis are widely shared by all. The need for transitions to be just and equitable arises out of the risk that adopting the most ambitious measures to reduce agricultural emissions could compromise food security and increase hunger, affecting the most vulnerable in society. Greater research and development; transition support for the most at risk and policy coherence; and government support are all critical factors in ensuring that a just transitions in agrifood systems benefits small holder food producers.